Which factors influence the anaphoric resolution of null objects and clitics in European Portuguese? A corpus study - Rinke, Esther (2024)
Based on a corpus study, this paper examines the relevance of pragmatic factors for the choice of the referent of a null object or a clitic in European Portuguese. The results show that both null objects and clitic pronouns are markers of high accessibility like null subjects, referring to referents recently and explicitly mentioned in discourse. However, they differ from null subjects in the absence of prolonged and uninterrupted reference chains, implying that null objects and object clitics have a distinct pragmatic and referential function from null subjects. We also demonstrate that both null objects and clitics preferably refer to antecedents with the syntactic function of an object, a syntactic parallelism that is only slightly attenuated in the case of null objects. Finally, the co-occurrence of both null objects and clitics with subject noun phrases indicates that a realized subject in the same sentence does not intervene in referential binding, and that null objects and clitics represent syntactic alternatives.